ASEM and the Bridging of the Human Security Gap - de Bruyn, Martyn (AEI Insights, 2021)
The European Union, recognizing the need to contribute to global security in the post-Cold War era, but lacking the capacity to act in international crisis situations, developed the European Security Strategy in 2003. The European Security Strategy, while not directly referring to the term human security, identifies key threats, such as terrorism, organized crime, and state failure, and unequivocally states: “Europe should be ready to share in the responsibility for global security and in building a better world.” Additionally, it states that cooperation between the EU and regional organizations such as ASEAN, MERCOSUR, and the African Union “make an important contribution to a more orderly world.” Given The EU’s extended commitment to human security, to the promotion of its values around the world, and to collaboration with other regional organizations, it is only natural that The EU, in its relations with ASEAN and a wider range of Asian states in ASEM (Asia Europe Meeting), promotes human security. ASEAN member states have also been engaged in discussions on human security. However, the focus has been exclusively on freedom from want (development) issues. The concept of freedom from fear, and the responsibility to protect (R2P), poses a critical challenge to ASEAN’s fundamental principles of independence, sovereignty, non-interference, and territorial integrity. This paper addresses the following two key concerns: (a) What is the rationale for human security promotion by the EU and ASEAN in the ASEM interregional cooperation framework? (b) While both The EU and ASEAN recognize the importance of the human security approach, their understanding of the concept of human security is distinctly different. Therefore, this paper investigates under what conditions The EU and ASEAN can come to a common understanding of human security.